Implementing Chain Writing in Report Text - Cherlinda, Dwi; Satria, Benni; Candra, Muhammad (Juliet, 2024)
The purpose of this research was knowing the effect of using the chain writing method on students’ writing achievement in writing report text at SMPN 1 Bintan. This research used quasi-experimental design. The population of this research was first semester 9th grade students at SMPN 1 Bintan with 30 students from two classes as a sample, 15 students in class 9.A as the experimental class using the chain writing method and 15 students in class 9.B as the control class. using the expository method. The treatment was conducted by researcher in November 2022. Then it can be concluded that students' writing achievement towards report text are not good enough. The results of data analysis, known that the chain writing method was no more effectively used in learning to write report text for 9th grade at SMPN 1 Bintan. From the results of the calculation of the independent T-test test one-tailed it was known that t0 obtained was 0.13, while ttable value in the degree of significance of 0.05 one-tailed test was 1.70 (df = 28). Because 0,13 < 1,70 the data from this research showed that there was a significant difference in the results of the posttest comparison of the two classes. This proved that the chain writing method was an ineffective method for learning report text for 9th grade students at SMPN 1 Bintan in the 2022/2023 academic year